Effect of humidity and thermal cycling on the catalyst layer structural changes in polymer electrolyte membrane fuel cells. (1st June 2019) - Chang, Yafei; Liu, Jing; Li, Ruitao; Zhao, Jian; Qin, Yanzhou; Zhang, Junfeng; Yin, Yan; Li, Xianguo
Highlights: Designed and conducted three sets of ex-situ experiments. Observed several key structural changes in catalyst layers. Obtained the dominant factor for cracks propagation in catalyst layers. Compared the performance of fresh and degraded catalyst layers. Abstract: Catalyst layer structural changes in polymer electrolyte membrane fuel cells have significant impact on the cell performance and durability. In this study, ex-situ experiments are designed to investigate the effect of humidity and/or thermal cycles on the structural changes of catalyst layers. The relative humidity and temperature are controlled by an environmental chamber and the catalyst layer structure is characterized by scanning electron microscopy and optical microscopy. The experimental results indicate that crack growth and development, catalyst agglomerate detachment, and surface bulges are the main structural changes of the catalyst layers. Applying relative humidity and thermal cycling simultaneously causes the most significant crack growth, while applying thermal cycling alone causes no appreciable changes. This indicates that the absolute humidity is the key parameter for the crack growth. Through cyclic voltammetry analysis, it is shown that the electrochemical active surface area decreases from 64.1 m 2  g −1 to 49.1 m 2  g −1 after 500 combined relative humidity and thermal cycles. Analyses of electrochemical impedance spectroscopy show that the charge transfer resistance and ohmic resistance increase significantly after 500 combined relative humidity and thermal cycles, causing the cell performance degradation.